2011
DOI: 10.1002/rcm.5182
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐cut dried blood spot (PCDBS): an alternative to dried blood spot (DBS) technique to overcome hematocrit impact

Abstract: Quantification of analytes by Dried Blood Spots (DBS) on different paper cards has been extensively reported in the past several years. However, some factors limit the robustness of the precision and accuracy of DBS such as: hematocrit level, blood viscosity, analyte nature, spotting technique and spotting conditions. As such, the paper material used for DBS must meet strict quality control criteria to produce reliable quantification of drugs: uniformity, no chemical leaching and no chromatographic effect. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 16 publications
2
80
0
2
Order By: Relevance
“…When no HT correction is applied, the method validation should include a range that covers substance concentration and a HT of the target population with the analytical re- , Jan-Willem C. Alffenaar 1* 1 sults within acceptable limits. The approach of whole spot analysis or pre-cut disks will show no effects of the HT on the spot formation [15][16][17][18]. However, if extraction efficiency is affected by HT and concentration of the substance, this effect cannot be compensated.…”
Section: The Influence Of Blood Hematocrit Value On Analytical Resultsmentioning
confidence: 99%
“…When no HT correction is applied, the method validation should include a range that covers substance concentration and a HT of the target population with the analytical re- , Jan-Willem C. Alffenaar 1* 1 sults within acceptable limits. The approach of whole spot analysis or pre-cut disks will show no effects of the HT on the spot formation [15][16][17][18]. However, if extraction efficiency is affected by HT and concentration of the substance, this effect cannot be compensated.…”
Section: The Influence Of Blood Hematocrit Value On Analytical Resultsmentioning
confidence: 99%
“…This technique could potentially be easily compatible with existing automation platforms with only minor modifications. Youhnovski et al published a similar concept named pre-cut dried blood spot (PCDBS) and reported good analytical performance and haematocrit independency (85) . Likewise Fan and Lee reported a similar commercially available approach named dried matrix in paper disc (DMPD) (86) .…”
Section: Haematocritmentioning
confidence: 99%
“…The requirement for accurate volume blood dispensing clearly compromises the simplicity of the original workflow that was envisioned for DBS, but the potential combined ethical, financial and logistic advantages on offer from DBS sampling still far outweigh the extra complexity and cost associated with an accurate volume DBS workflow, if practical accurate volume collection methods can be utilised (23,59) . In the last few years, new technology and whole blood dispensing techniques have been reported that potentially make accurate volume spotting, and whole-spot sample extraction options a realistic proposition (84,85,86,61,64,65,63) . New blood collection technologies such as the DBS-System (from Déglon et al), and Mitra or volumeric absorptive microsampling (VAMS) (from Phenomenex, albeit in a different format to card based DBS) demonstrate that practical, and cost effective solutions to accurate volume blood microsampling are available (63,130) .…”
Section: Introductionmentioning
confidence: 99%
“…Varied hematocrit value in different persons especially in diseased state is the limitation of the DBS technique. However impact of hematocrit value in bioanalysis using DBS samples was widely discussed and possible solutions were elucidated [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%